Implementation of State-Owned Assets Management Policy: An Analysis of Asset Management, Disposal, and Write-Off Based on the Edward III Model at the Palembang Religious Training Center - Rahmawati Rahmawati; Lili Erina; Nurmah Semil; Raniasa Putra (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
This study aims to examine the implementation of Government Regulation of the Republic of Indonesia No. 28 of 2020 regarding the management of State-Owned Assets (BMN), specifically in terms of the administration, destruction, and write-off of state-owned assets at the Palembang Religious Training Center. A qualitative approach with a case study design was employed. Data were collected through interviews, observations, and documentation, and were analyzed using the Miles, Huberman, and Saldaña interactive model within the framework of George Edward III’s policy implementation theory. The results indicate that the implementation of the BMN management policy has not yet reached an optimal state. The primary issues lie in weak organizational communication, limited resource capacity, low commitment among implementers, and the lack of integration within the bureaucratic structure. These conditions result in discrepancies in BMN data, delays in administrative processes, and the ineffective execution of BMN disposal and write-off procedures. This study contributes to strengthening the application of Edward III’s theory within the context of state-owned asset management at the work unit level, while also expanding the analysis to include aspects of BMN disposal and write-off. The research implications emphasize the need to strengthen internal coordination, enhance human resource capacity, provide proportional incentives, and improve the bureaucratic system to make it more integrated.